Influence of particle size and concentration on the second-harmonic signal generated at colloidal surfaces - Schneider, L.; Schmid, Hans-Joachim; Peukert, Wolfgang (Applied Physics B-Lasers and Optics, 2007)
Second harmonic generation (SHG) spectroscopy is a recently developed technique for the investigation of surface properties of particles. To apply the method to technical colloidal systems, the dependences of several experimental parameters on the signal have to be studied. In this work the influence of particle concentration on the SHG signal from the surfaces of colloids (polystyrene beads in a size range of 0.1 mu m to 2.9 mu m) is investigated. A simple model, based on Lambert-Beer's law, to describe the measured dependences is derived. The model agrees with the experimental observations for particles smaller 1.1 mu m and with a small modification also for larger particles. Based on the new model an analytical equation for determining the optimum concentration, where highest signals in colloidal SHG spectroscopy measurements are obtained, is derived.